A influência da indústria 4.0 no setor da contabilidade - Ferreira, Carina Gonçalves (2021)
The evolution of information technologies has been driving great social transformations. In the business world, this transformation translates into a redefinition of industrial structure and business models. Financial services and activities, namely accounting services, are facing the challenge of a paradigm shift regarding work processes, in order to adapt their business models to the digital economy era and, at the same time, being drivers of digital transformation of Small and Medium Enterprises. This work intends to evaluate the influence of Industry 4.0 in the accounting sector. In this sense, the following research questions were defined: Do accounting firms have a perception of the changes and the contribution with the adoption of the new software? What were the main challenges and barriers? What were the main advantages? Is there credibility and reliability in these new technologies? What is the impact that the digital transformation had on the leader at the level of distribution and restructuring of tasks? Is it manifested those professionals are engaged or resistant to change? In addition to the specific competences of the fundamental areas of the accounting course, what competences will accountants need to acquire in order to be able to practice the profession in the near future? The study follows a qualitative and exploratory approach, using semi-structured interviews and other data sources referring to the four cases under study. The results obtained show that, despite new technologies being a challenge for professionals and organizations, it is up to accountants to work on the development of their digital skills to be the organizations’ interlocutors in the digitalization processes. It is necessary for the accountant to become multifaceted and able to reinvent himself in the profession.